Sex differences impact the lung-bone inflammatory response to repetitive inhalant lipopolysaccharide exposures in mice. (1st January 2018) - Nelson, Amy J.; Roy, Shyamal K.; Warren, Kristi; Janike, Katherine; Thiele, Geoffrey M.; Mikuls, Ted R.; Romberger, Debra J.; Wang, Dong; Swanson, Benjamin; Poole, Jill A.
Abstract: Skeletal health consequences associated with inflammatory diseases of the airways significantly contribute to morbidity. Sex differences have been described independently for lung and bone diseases. Repetitive inhalant exposure to lipopolysaccharide (LPS) induces bone loss and deterioration in male mice, but comparison effects in females are unknown. Using an intranasal inhalation exposure model, 8-week-old C57BL/6 male and female mice were treated daily with LPS (100 ng) or saline for 3 weeks. Bronchoalveolar lavage fluids, lung tissues, tibias, bone marrow cells, and blood were collected. LPS-induced airway neutrophil influx, interleukin (IL)-6 and neutrophil chemoattractant levels, and bronchiolar inflammation were exaggerated in male animals as compared to female mice. Trabecular bone micro-CT imaging and analysis of the proximal tibia were conducted. Inhalant LPS exposures lead to deterioration of bone quality only in male mice (not females) marked by decreased bone mineral density, bone volume/tissue volume ratio, trabecular thickness and number, and increased bone surface-to-bone volume ratio. Serum pentraxin-2 levels were modulated by sex differences and LPS exposure. In proof-of-concept studies, ovarectomized female mice demonstrated LPS-induced bone deterioration, and estradiol supplementation of ovarectomized female mice and control male mice protected against LPS-induced bone deterioration findings. Collectively, sex-specific differences exist in LPS-induced airway inflammatory consequences with significant differences found in bone quantity and quality parameters. Male mice demonstrated susceptibility to bone loss and female animals were protected, which was modulated by estrogen. Therefore, sex differences influence the biologic response in the lung-bone inflammatory axis in response to inhalant LPS exposures.